Analysis of the Determinants of Consumer Behavior in Purchasing PE Goats in Purworejo Regency - Indah Purwaningsih; Hesti Respatiningsih; Dewi Shanti Nugrahani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study was to see how cultural, social, personal and psychological factors can shape consumer decisions in Purworejo Regency in purchasing PE goats. This study used a quantitative approach with a sample size of 110 respondents. Data analysis was carried out through multiple linear regression, t-test and F-test. The results showed that simultaneously the four factors had a significant effect on purchasing decisions for PE goats. However, partially, only social and psychological factors had a significant effect, while cultural and personal factors did not show a significant effect. This finding emphasizes the importance of a marketing approach that considers the influence of the social environment and psychological drives of consumers in purchasing decisions. The implications of this study indicate that an understanding of social and psychological factors can be utilized to strengthen product promotion and communication strategies in the PE goat farming sector.